(untitled) (Comprehensive Journal of Science, 2026)
Corruption poses a significant challenge to Libyan society amidst the political and social transformations the country is undergoing. This research focuses on the legal and social specificities related to corruption crimes in Libya, with an emphasis on how Libyan criminal legislation addresses these crimes in terms of prevention, criminalization, and punishment. The research aims to analyze the legal frameworks governing anti-corruption efforts in Libya, as well as the social and cultural factors influencing the application of these laws. The research also aims to offer recommendations for improving legislation and procedures related to combating corruption in Libya.